Clinical dental students' perceptions of difficulties in fixed prosthodontics bridgework denture preparation: a pilot study - Sarwono, Aditya Pratama; Febianti, Khairunnisa (Intelektual Pustaka Media Utama, 2025)
Preparing abutment teeth for fixed bridgework presents varying challenges to dental students, impacting their training effectiveness and clinical outcomes. Understanding the most difficult stages can help improve educational strategies. This study aims to rank the difficulty of each stage in abutment tooth preparation using student evaluations, identifying the greatest challenges. A quantitative approach was used, analyzing perceptions of 155 clinical dental students from 2021-2023 cohorts at Faculty of Dentistry, Universitas Trisakti, through the non-parametric Friedman’s ANOVA Test. Student evaluations covered seven stages of abutment tooth preparation, identifying variability in perceived difficulty from most difficult to easiest. Results indicate the most difficult stage is proximal reduction (mean rank: 3.01), followed by cervical preparation (mean rank: 3.28), and lingual reduction (mean rank: 3.35). The stages with the lowest difficulty are finishing (mean rank: 5.35), followed by alignment of preparation between 2 abutment teeth (mean rank: 4.85), buccal reduction (mean rank: 4.13), and occlusal reduction (mean rank: 4.03). Proximal reduction is particularly difficult due to the need for high technical skills and precision, requiring accurate space estimation and careful reduction without damaging adjacent teeth. This difficulty is compounded by natural variations in tooth shapes and positions among patients. Findings highlight the importance of refining educational strategies to tackle these challenges, enhancing student learning and clinical skills. This research provides crucial data on which stages need greater emphasis in the curriculum, aiding the creation of more efficient and focused training methods.